Structural, spectroscopic and biological study of trifluoroethyl methansulfonate (methylsulfonyl), TFMSMS - Galván, Jorge Edgardo (2022)
Trifluoroethyl methansulfonate (methylsulfonyl), TFMSMS is a new compound derived from Clomesone, which was obtained in solid state. As no experimental geometric parameters were available, a conformational exploration was carried out (using the concept of “conformational transferability”), resulting a single stable conformation at room temperature. Infrared, Raman, and liquid NMR spectra were measured. The contributions of the donor → acceptor interaction energies were also analyzed by Natural Bond Orbitals (NBO) approximations and topological properties (AIM). These results evidenced that electron delocalization and especially LP O→σ*O(3)-C(3) interaction play an important role in the reactivity-structure connection of oxoesters and thioesters. TFMSMS could partially inhibit growth and biofilm formation on Pseudomonas aeruginosa and Staphylococcus aureus strains. Moreover, this is the first study demonstrating the methansulfonate complex interference with the Quorum sensing system in Gram-negative bacteria.